The Narrative of Women and Local Wisdom in Modern Indonesian Films: A Study of Culture and Gender - Nurwafiqah Amirah Budi,; Rosdiawati, Rosdiawati; Elihami, Elihami; Wulandari,; Haerusman, (Edumaspul: Jurnal Pendidikan, 2026)
The development of contemporary Indonesian cinema shows an interesting transformation in the representation of women and local cultural values. Films function not only as entertainment media but also as social discourse that reflects societal views on gender and tradition. This study aims to examine how women are represented as symbols of local wisdom in contemporary Indonesian films. The research uses a descriptive qualitative approach, drawing on Stuart Hall’s theory of representation and Elaine Showalter’s perspective on cultural feminism to analyze the symbolic meanings embedded in film narratives.